PROSTHETIC PROBLEMS OF TRANSTIBIAL AMPUTEE - Ahmad, Aziz (Journal of Postgraduate Medical Institute, 2011)
Objective: To investigate the challenges faced by Prosthetist in the management of Transtibial amputees. Material and Methods: This study was conducted at Department of Prosthesis and Orthosis Pakistan Institute of Prosthetic and Orthotic Sciences, Hayatabad, Peshawar, Pakistan in 2008. The data was collected via a survey questionnaire distributed among 26 Prosthetists and Orthotists. The collected data was analyzed with 95% confidence interval. Descriptive statistical analysis was used. Results: Eighty five percent (n=22/26) of the questionnaires were received back within the given time of two weeks. Majority of the respondents agreed that they do face problems like volume fluctuation, fibula left longer than tibia, redundant tissues and phantom pain etc in a transtibial amputee (TTA). Furthermore, gender, cause of amputation, weight and age are the factors which makes the rehabilitation process difficult. Conclusion: Along with the patient and his family, Prosthetist is also faced with difficulties in transtibial amputees during the process of rehabilitation with prosthetic fitting.